HIV Transmission Misconceptions and Their Associated Factors Among Reproductive-Age Women in Somalia: Findings from a Nationwide Study - Mohamud LA; Hassan-Kadle MA; Abdullahi HM; Ahmed AA (Infection and Drug Resistance)
Liban Ali Mohamud,1 Mohamed Abdulkadir Hassan-Kadle,2,3 Hamza Mohamed Abdullahi,4 Ahmed Ali Ahmed5 1Department of Statistics and Planning, SIMAD University, Mogadishu, Somalia; 2College of Medicine and Health Science, Abrar University, Mogadishu, Somalia; 3Center for Digestive and Liver Diseases, Waaberi Hospital, Mogadishu, Somalia; 4National HIV Program, Federal Ministry of Health, Mogadishu, Somalia; 5Somdoctor Health Services, Mogadishu, SomaliaCorrespondence: Mohamed Abdulkadir Hassan-Kadle, Email dr.kadle@abrar.edu.soBackground: Human Immunodeficiency Virus (HIV) remains a significant public health challenge, particularly in low-resource settings, where limited knowledge contributes to its spread, especially among women facing socio-economic and educational barriers. This study examines the associations between misconceptions about HIV transmission and sociodemographic factors among Somali women. Identifying regions and groups with limited awareness will help prioritize targeted education and healthcare interventions, aligning with the National Strategic Plan (NSP).Methods: A multivariable Bayesian logistic regression model was used to analyze data from the 2018– 2019 Somali Demographic and Health Survey (SDHS). This modeling approach was chosen for its ability to handle uncertainty and incorporate prior knowledge into the analysis. Bayesian adjusted odds ratios (BAORs) with 95% highest posterior density intervals (HPDIs) were calculated to determine significant associations between misconceptions and sociodemographic factors.Results: The study found that 67.18% of women had misconceptions about HIV transmission. Significant factors associated with misconceptions included age, education, wealth, and internet usage. Women aged 30– 34 (BAOR = 0.94, 95% HPDI: 0.90– 0.98), 35– 39 (BAOR = 0.94, 95% HPDI: 0.90– 0.98), and 40– 44 (BAOR = 0.93, 95% HPDI: 0.89– 0.98), women with secondary education (BAOR = 0.92, 95% HPDI: 0.88– 0.95), women with higher education (BAOR = 0.84, 95% HPDI: 0.79– 0.88), women in the highest wealth quintile (BAOR = 0.90, 95% HPDI: 0.86– 0.95), and women who had never used the internet (BAOR = 1.06, 95% HPDI: 1.03– 1.09).Conclusion: This study highlights the critical need for targeted interventions to reduce misconceptions about HIV transmission among Somali women. Policies should focus on educating younger women, promoting female education, implementing region-specific health interventions, and enhancing internet access and digital literacy, particularly in rural areas, to improve HIV knowledge and support public health efforts.Keywords: HIV misconceptions, Somali women, digital literacy, bayesian analysis, highest posterior density interval, bayesian adjusted odds ratios, public health interventions